Decision model to identify the optimum retaining wall type for restricted highway projects sites. Issue 8 (11th June 2023) - Mahdi, Ibrahim M.; Arafat, Hisham; Ebid, Ahmed M.; El-Kadi, Anwar F.
Abstract: Choosing the suitable soil retaining system is the key to optimizing the design of the restricted sites highway projects. Many parameters are involved in identifying the optimum choice. This research approaches a decision support system (DSS) to determine the level of suitability of each alternative in order to identify the most optimal choice. In this approach, an integration of the value engineering (VE) hypothesis with the analytical hierarchy process (AHP) is implemented to form the DSS to determine the relative importance of the factors affecting selection. This research includes four of the most applied retaining wall types: cemented sand, stone gravity wall, RC cantilever wall and the mechanically stabilized wall (MSW). The developed DSS was verified via four case studies of highway projects in the construction stage. In three out of the four case studies, the optimal choice was in accordance with the proposed DSS. The research also showed that fully slopped embankments are the optimum choice for unrestricted sites up to a certain land cost, beyond which fully retained embankments became the optimum choice.